농협중앙회 자회사 활성화 방안연구 - 황의식 (한국농촌경제연구원, 2008)
The purpose of this study is to establish the business innovation strategies of the subsidiaries in the National Agricultural Cooperative Federation (NACF). We expect our study will help set up the innovation strategy to adopt more quickly in changing environment of agricultural market, hence acquiring competitive power in the long run. The reason for academics to request subsidiaries in the NACF is that the believe the NACF has not taken important role in marketing Fist analyzed the business structure of the subsidiaries in the NACF and NACF, then summarized the current condition and problems. Second learned from the the experiences of developed countries(Japan, German, Netherlands), then evaluated the adequacy of the plan to revitalized subsidiaries in the NACF. Third, interviewd with the executive secretary of agricultural cooperatives for status quo of using subsidiaries in the NACF and innovation strategies to build a self-reliance of subsidiaries. Fourth and last, came up with basic principle, system, and rule modifying scheme for plan to revitalize organization in the NACF and proposed our won plan coping with market opening of agricultural products, and the change in marketing environment. Researchers: Eui-Sik Hwang, Joo-Nyung Heo, Gwang-Seok Chae E-mail address: eshwang@krei.re.kr, knuhjn@krei.re.kr, gschae@krei.re.kr